Chloroquine Drug Interactions Part II -- Interaction with Diuretics (The East and Central African Journal of Pharmaceutical Sciences, 2020)
Chloroquine, a commonly used antimalarial agent was investigated for interaction with common diuretics, furosemide and chlorthiazide. Examination of urine samples collected from water loaded rats at hourly intervals revealed that chloroquine antagonized the furosemide and chlorthiazide induced diuresis. It also decreased the natriuretic and enhanced the kaliuretic effects of furosemide and chlorthiazide.
Keywords: Chloroquine, furosemide, chlorthiazide, drug interaction, diuretics, kaliuresis, natriuresis